Intensive and Extensive Speaking Instructional Approaches: Model Pembelajaran Keterampilan Berbicara Tingkat Menengah Bagi Mahasiswa Calon Guru Bahasa Inggris - Baso Jabu; Chairil Anwar Korompot (Seminar Nasional LP2M UNM, 2019)
In the implementation of an Intensive Speaking Instructional Approach (ISIA) to speaking skills development, instructions and activities occur mostly in the classroom. They are initiated mostly by the instructor (lecturer/teacher) and designed for students. The instructor plans and selects materials, guides and manages activities and exercises in the classroom, gives feedback, and assesses students’ accomplishments. On the contrary, in an Extensive Speaking Instructional Approach (ESIA), speaking skills development occurs mostly outside the classroom involving the instructor, the students, and various other people. It is based on topics selected, developed, discussed, responded to, and even assessed by the students themselves. This paper reports on research study that investigates the use of ISIA and ESIA to develop an instructional model for the Intermediate Speaking course designed for student teachers of English attending the third semester of their degree course. It presents one of the most important findings of the study, which is the instructional model. The model includes a syllabus consisting of the Intermediate Speaking instructional units, objectives of each of the instructional units, formative and summative assessment, instructional procedures or strategies, and the course materials